Clinical prediction rules for failed nonoperative reduction of intussusception - Khorana J; Patumanond J; Ukarapol N; Laohapensang M; Visrutaratna P; Singhavejsakul J (Dove Medical Press, 2016)
Jiraporn Khorana,1 Jayanton Patumanond,2 Nuthapong Ukarapol,3 Mongkol Laohapensang,4 Pannee Visrutaratna,5 Jesda Singhavejsakul1 1Department of Surgery, Division of Pediatric Surgery, Chiang Mai University Hospital, Chiang Mai, 2Center of Excellence in Applied Epidemiology, Thammasat University Hospital, Bangkok, 3Department of Pediatrics, Division of Gastroenterology, Chiang Mai University Hospital, Chiang Mai, 4Department of Surgery, Division of Pediatric Surgery, Siriraj Hospital, Mahidol University, Bangkok, 5Department of Radiology, Chiang Mai University Hospital, Chiang Mai, Thailand Purpose: The nonoperative reduction of intussusception in children can be performed safely if there are no contraindications. Many risk factors associated with failed reduction were defined. The aim of this study was to develop a scoring system for predicting the failure of nonoperative reduction using various determinants.Patients and methods: The data were collected from Chiang Mai University Hospital and Siriraj Hospital from January 2006 to December 2012. Inclusion criteria consisted of patients with intussusception aged 0–15 years with no contraindications for nonoperative reduction. The clinical prediction rules were developed using significant risk factors from the multivariable analysis.Results: A total of 170 patients with intussusception were included in the study. In the final analysis model, 154 patients were used for identifying the significant risk factors of failure of reduction. Ten factors clustering by the age of 3 years were identified and used for developing the clinical prediction rules, and the factors were as follows: body weight <12 kg (relative risk [RR] =1.48, P=0.004), duration of symptoms >48 hours (RR =1.26, P<0.001), vomiting (RR =1.63, P<0.001), rectal bleeding (RR =1.50, P<0.001), abdominal distension (RR =1.60, P=0.003), temperature >37.8°C (RR =1.51, P<0.001), palpable mass (RR =1.26, P<0.001), location of mass (left over right side RR =1.48, P<0.001), ultrasound showed poor prognostic signs (RR =1.35, P<0.001), and the method of reduction (hydrostatic over pneumatic, RR =1.34, P=0.023). Prediction scores ranged from 0 to 16. A high-risk group (scores 12–16) predicted a greater chance of reduction failure (likelihood ratio of positive [LR+] =18.22, P<0.001). A low-risk group (score 0–11) predicted a lower chance of reduction failure (LR+ =0.79, P<0.001). The performance of the scoring model was 80.68% (area under the receiver operating characteristic curve).Conclusion: This scoring guideline was used to predict the results of nonoperative reduction and forecast the prognosis of the failed reduction. The usefulness of these prediction scores is for informing the parents before the reduction. This scoring system can be used as a guide to promote the possible referral of the cases to tertiary centers with facilities for nonoperative reduction if possible. Keywords: intussusception, nonoperative reduction, failure rate, clinical prediction rules